Staging cultural encounters Algerian actors tour the United States - Goodman, Jane E. 1956- (Bloomington, Indiana Indiana University Press, 2020)
Staging Cultural Encounters tells stories about performances of cultural encounter and cultural exchange during the US tour of the Algerian theater troupe Istijmam Culturelle in 2016. Jane E. Goodman follows the Algerian theater troupe as they prepare for and then tour the U.S. under the auspices of the Center Stage program, sponsored by the US State Department to promote cross-cultural dialogue and understanding. The title of the play Istijmam produced was translated as'Apples,'written by Abdelkader Alloula, a renowned Algerian playwright, director, and actor who was assassinated in 1994. Goodman take readers on tour with the actors as they move from the Kennedy Center in Washington, D.C. to the large state universities of New Hampshire and Indiana, and from a tiny community theater in small-town New England to the stage of the avant-garde La MaMa Theater in New York City. Staging Cultural Encounters takes up conundrums of cross-cultural encounter, challenges in translation, and audience reception, offering a frank account of the encounters with American audiences and the successes and disappointments of the experience of exchange.
1. The customer and the attendant: desire, disappearance, and disenfranchisement in neoliberalizing Algeria -- 2. Restaging the Halqa: From Algerian market to global marketplace -- 3. On the road: cultural encounters in cosmopolitan times -- 4. Behind the scenes: the disciplines of rehearsal -- 5. Encounters in translation: How Et-Teffeh became apples -- Epilogue: apples in America.
Includes bibliographical references (pages 231-244) and index.
Keywords: Theatrical companies -- Algeria -- History -- 21st century; Algerians -- United States -- History -- 21st century